A Study on AIS Quality in the use of the ERPS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2020)
The use of the Enterprise Resource Planning Systems (hereafter, ERPS) in India showed a significant  growth. This growth has lead to the need to have an empirical evidence about the accounting  benefits from using that systems. The existences of accounting research on ERPS has created an  opportunity for further research on the Accounting Information Systems (AIS) quality and effectiveness  in the decision making process related to the level of the use of the ERPS. This research is using  alternative methods of Partial Least Square (PLS}. The result suggest that the manager's perceptions  of the AIS quality affect the effectiveness of the decision making process. The breadth of the use  of the ERPS can be a moderating factor in the relationship between manager's perception of the  AIS quality and the effectiveness of the decision-making process. Finnally, there was no difference  between the perceptions of the different department managers regarding the AIS quality and the  effectiveness of the decision making process on the breadth of the use of the ERPS.
Keywords: ERPS capabilities; AIS quality; Decision Making Process Effectiveness; manager